PEGylated lipid polymeric nanoparticle–encapsulated acyclovir for in vitro controlled release and ex vivo gut sac permeation - Mahmood, Syed; Kong, Chak Kiong; Chun, Shern Tham; Tan, Choo Chien; Ayah Rebhi, Hilles; Venugopal, Jayarama Reddy (Springer Science and Business Media Deutschland GmbH, 2020)
Currently, pharmaceutical research is directed wide range for developing new drugs for oral administration to target disease. Acyclovir formulation is having common issues of short half-life and poor permeability, causing messy treatment which results in patient incompliance. The present study formulates a lipid polymeric hybrid nanoparticles for antiviral acyclovir (ACV) agent with Phospholipon® 90G (lecithin), chitosan, and polyethylene glycol (PEG) to improve controlled release of the drugs. The study focused on the encapsulation of the ACV in lipid polymeric particle and their sustained delivery. The formulation developed for the self-assembly of chitosan and lecithin to form a shell encapsulating acyclovir, followed by PEGylation. Optimisation was performed via Box-Behnken Design (BBD), forming nanoparticles with size of 187.7 ± 3.75 nm, 83.81 ± 1.93% drug-entrapped efficiency (EE), and + 37.7 ± 1.16 mV zeta potential. Scanning electron microscopy and transmission electron microscopy images displayed spherical nanoparticles formation. Encapsulation of ACV and complexity with other physical parameters are confirmed through analysis using Fourier transform infrared spectroscopy, differential scanning calorimetry, and X-ray diffraction. Nanoparticle produced was capable of achieving 24-h sustained release in vitro on gastric and intestinal environments. Ex vivo study proved the improvement of acyclovir’s apparent permeability from 2 × 10−6 to 6.46 × 10−6 cm s−1. Acyclovir new formulation was achieved to be stable up to 60 days for controlled release of the drugs.